Comparative Study on Calculation Method of Contact Force in Joint with Clearance of Crank Slider Mechanism - Tingting Li; Zhenshan Zhang; Guohua Cui; Lianzhe Guan (Jixie chuandong)
In order to select the best contact force calculation method for the dynamics performance analysis of multibody systems involving joints with clearance， a dynamics model of a crank slider mechanism involving joints with clearance is established and a systematic comparative analysis is performed for calculation methods of contact force with the crank slider mechanism involving joints with clearance as the object. The influence of the calculation method of contact force on dynamics performance analysis of the crank slider mechanism under different clearances， crank speeds and recovery factors is studied. The analysis results show that when studying the influences of changes in radial clearance， driving load， and recovery coefficient on dynamics of multibody systems， both the Lankarani-Nikravesh contact force model and the ZhiYing-QiShao contact force model are relatively reliable， and the ZhiYing-QiShao contact force model is the least sensitive to the recovery coefficient.